Designing a Child Behavior Disorder Expert System Database Using the Database Life Cycle Method - Nurhayati, Nurhayati; Nur Rahmawati, Eni; Dwi Anand Sinar Putra, Imanuel; Rizky Maulana, Dimas (LPPM Universitas Duta Bangsa Surakarta, 2024)
Behavioral disorders in children are complex issues that require careful handling in order to avoid affecting their future development. An expert system has been developed to assist parents, teachers, and health professionals in diagnosing and treating various types of behavioral disorders in children. A well-designed database is essential for an effective expert system, ensuring integrity, availability, and optimal performance. This research aims to design a database for an expert system for behavioral disorders in children using the database life cycle method. The study employs relational database design, including conceptual, logical, and physical design and implementation in MySQL DBMS. The results of the study indicate that the database design approach, including conceptual, logical, and physical databases, can produce an efficient database that adheres to the principles of a relational database.